Psychometric properties of a color-shape version of the switch task. Issue 5 (3rd September 2022) - Sicard, Veronik; Moore, Robert Davis; Simard, Alexe; Lavoie, Gabriel; Ellemberg, Dave
Abstract: The current study aims to examine the psychometric properties of a color-shape version of the switch task. In Study 1, 128 participants completed a battery of standardized measures of executive functions (EFs) as well as the switch task to determine the construct validity of three traditionally computed costs (global, switch, and mixing) and primary variables (accuracy [ACC], reaction time [RT], and inverse efficiency score [IES] of the heterogeneous condition). In Study 2, 48 participants completed the task twice, seven days apart, to evaluate its short-term test-retest reliability. Results do not support the construct validity and the test-retest reliability of switch and mixing costs. The overall higher psychometric properties of the global costs (RT and IES), and primary variables (Hetero RT and IES) suggest that they may be useful measures for clinicians to assess EFs. The latter variables show evidence of convergent validity with standardized measures of EFs and good test-rest reliability (ICC ≥ .68).